Simulações da utilização do grafeno no processo de modulação de fase em sinais ópticos - Casallas, Fabiana Campos (2017)
This work presents studies and simulations of phase modulators in optical signals with the use of integrated components based on silicon photonics with graphene to improve the data transmission capacity (bandwidth) due to the increasing demand generated by new and modern last generation used in industries and residences nowaday. A brief description of the history of research on graphene, its characteristics and challenges in the area of phase modulation will be presented, emphasizing the applications with modulation by electro-refraction. Through numerical simulations, optical phase modulators based on silicon waveguides with graphene transferred on these guides were designed, quasi-TE and quasi-TM modes were evaluated. Although most graphene-based integrated modulators have been shown to operate in quasi-TE mode, this work demonstrates that the best performance achieved was for quasi-TM mode operation due to a higher concentration of the optical field in the region where the graphene is deposited on the waveguide. The best performance was achieved for a waveguide formed by silicon with 2 layers of graphene in its upper part, separated by a dielectric alumina material, with operation in the quasi-TM mode, with VpL of 0,5 V.mm and electro-optical bandwidth up to 2,85 GHz.